Cadre Assistance in Efforts to Prevent Stunting Using Snakes and Ladders Game for Pregnant Women in Penyengat Olak Village, Muaro Jambi Regency: Pendampingan Kader Dalam Upaya Pencegahan Stunting Dengan Permainan Ular Tangga Untuk Ibu Hamil Di Desa Penyengat Olak Kabupaten Muaro Jambi - Ika Murtiyarini; Pauline Kusmaryati (Yayasan Ahmar Cendekia Indonesia, 2024)
Stunting is still a problem in Indonesia, including in Jambi Province. Based on the Indonesian Nutrition Status Report (SSGI), the prevalence of children under five years of age (toddlers) who experience stunting in Jambi Province is 22.4% in 2021. This causes irreversible disruption to children's physical development, causing a decrease in cognitive abilities and stunting. physical growth, mental development and health status in children. Stunting causes poor cognitive abilities, low productivity, and an increased risk of disease resulting in long-term losses for the Indonesian economy. One way to prevent stunting is to provide nutritional and health services to pregnant women. The government's acceleration of nutritional improvements has made the First Thousand Days of Life (1000 HPK) a strategic priority in preventing stunting. The consequences of malnutrition at 1000 HPK are permanent and difficult to repair. One promotional effort that can be made to increase pregnant women's knowledge about preventing stunting is by implementing the snakes and ladders game in pregnant women's classes. The snakes and ladders game as a health promotion medium is an effective tool in providing information and is able to increase knowledge and attitudes. This educational activity was carried out for 40 cadres and pregnant women. This activity is carried out directly using snakes and ladders related to stunting, including understanding stunting, recognizing signs of stunting, preventing stunting, causes of stunting, impacts of stunting, as well as tips for preventing stunting during the first 1000 days of life (HPK). The game activities went well and received a good response and enthusiasm from the cadres and pregnant women. This was demonstrated by the cadres' enthusiasm in asking questions and playing snakes and ladders. Next, the cadre led a game of snakes and ladders for pregnant women. The education provided was also delivered well, as shown by the increase in cadres' knowledge regarding stunting by looking at the increasing comparison of pre-test and post-test results. Play and educational activities using snakes and ladders need to continue to be implemented as an effort to increase cadres' knowledge in educating pregnant women in preventing stunting.